Penerapan Terapi Suportif Dan Psikoedukasi Keluarga Terhadap Ansietas Klien Hipertensi Menggunakan Pendekatan Keperawatan Transkultural - Pinilih, Sambodo Sriadi; Daulima, Novy Helena Catharina; Hargiana, Giur (Borobudur Nursing Review, 2025)
Hypertensive clients are at risk of experiencing anxiety that affects their quality of life. Treatment of hypertension takes a long time, the condition decreases with age, and the need for adaptation to the condition of the illness, will cause psychosocial problems in people with chronic diseases such as hypertension. Physical treatment alone is not enough, because the occurrence of hypertension and anxiety problems affect each other. The purpose of this final scientific paper is to provide an overview of the application of psychological nursing therapy, supportive therapy and psychoeducation of anxiety problems in hypertensive clients using a transcultural nursing approach. This scientific work uses a case study method, data collection using an anxiety symptom instrument and the Hamilton Anxiety Rating Scale (HARS). Psychiatric nursing actions were given to 19 hypertensive clients with anxiety nursing problems. The results of the application reduced the mean signs and symptoms of anxiety in the intervention group with supportive therapy and psychoeducation by 41.5%. The decrease in the mean difference in anxiety level scores from moderate anxiety to not anxiety is 13.8. Meanwhile, in the control group, only family psychoeducation was given to decrease the symptoms of 39.6% and the difference in the mean score of the anxiety level was 11.3. The conclusion is that both groups experienced a decrease in symptoms and scores on anxiety levels, but the score decreased more in the client group after being given family psychoeducation with supportive therapy. This final scientific paper recommends that the puskesmas can continue nursing actions for supportive group therapy on an ongoing basis, to reduce signs and symptoms and the level of attention in hypertensive clients.